2008
DOI: 10.1093/occmed/kqn018
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a screening programme for lung cancer in former asbestos workers

Abstract: Screening adherence and frequency of detection were low, while costs and radiation dose were high. In spite of a high cumulative asbestos exposure, lung cancer risk was not increased relative to the general population. The screening programme was not felt to be cost-effective from the perspective of the government as a third-party funding agency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 18 publications
1
21
0
3
Order By: Relevance
“…Asbestos health monitoring guidelines were published by the Spanish Health Minister in 2003 (24) and by French Haute Autoritè de Santè in 2010 (25). In Italy a consensus document developed by experts was developed in 2012 (13) after several experiences carried out in the previous two decades (5,7,(26)(27)(28)(29)(30)(31)(32)(33). Anyhow, official specific recommendations of the Italian Health Minister are not available yet.…”
Section: Discussionmentioning
confidence: 99%
“…Asbestos health monitoring guidelines were published by the Spanish Health Minister in 2003 (24) and by French Haute Autoritè de Santè in 2010 (25). In Italy a consensus document developed by experts was developed in 2012 (13) after several experiences carried out in the previous two decades (5,7,(26)(27)(28)(29)(30)(31)(32)(33). Anyhow, official specific recommendations of the Italian Health Minister are not available yet.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that lung screening with LDCT is useful in asbestos-exposed subjects at least as in strong smokers. On the contrary, Mastrangelo et al (32), in an observational study performed in Padova, evaluated over 1,119 exposed subjects (mean age, 57 years; mean exposure, 123 fibers/mL × year; 65% smokers) and identified 5 lung cancers (detection rate 0.4%), 1 at stage 1; no mesothelioma was found. In this paper lung cancer screening with LDCT was not considered cost-effective.…”
Section: Ldct Lung Cancer Screening In Asbestos-exposed Workersmentioning
confidence: 98%
“…From 2002 to 2009, the results of some lung cancer screening trials with LDCT on asbestos-exposed workers were published (29)(30)(31)(32)(33)(34). Unfortunately, in these studies CT image acquisition and reconstruction algorithms are different as well as technical parameters (mA, slice thickness, reconstruction interval, additional HRCT slices, etc.…”
Section: Ldct Lung Cancer Screening In Asbestos-exposed Workersmentioning
confidence: 99%
See 1 more Smart Citation
“…If a subject changed job or factory the cumulative exposure was the sum of products (Σ (i × f × l)). The interviewers were trained in the use of the questionnaire in order to minimize the information bias [8]. Length of exposure (years), time elapsed since first and last exposure (years), peak asbestos level (highest asbestos exposure for any job held, fibers/ml) and cumulative asbestos exposure (fibers×years/ml) have been considered in the present study.…”
Section: Assessment Of Occupational and Environmental Exposurementioning
confidence: 99%